2013
DOI: 10.1260/1756-8315.5.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Flame Color as a Lean Blowout Predictor

Abstract: The study characterizes the behavior of a premixed swirl stabilized dump plane combustor flame near its lean blow-out (LBO) limit in terms of CH* chemiluminiscence intensity and observable flame color variations for a wide range of equivalence ratio, flow rates and degree of premixing (characterized by premixing length, L fuel ). LPG and pure methane are used as fuel. We propose a novel LBO prediction strategy based solely on the flame color. It is observed that as the flame approaches LBO, its color changes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Let the alphabet size be k = || and the method of partitioning the time series be maximum entropy partitioning [31], i.e., a uniform probability distribution on the symbols with Then, the information loss, represented by the negative of the entropy [21] of the symbol sequence, is given as (11) By representing the computational complexity as a function g(k) of the alphabet size k and choosing an appropriate scalar tradeoff weighting parameter a  (0, 1), the cost functional to be optimized becomes: (12) The optimal alphabet size || is obtained by solving for k in the equation J(k + 1) -J(k) = 0 along with additional constraints that may have to be imposed in the optimization procedure to realize the effects of critical issues such as any bounds on the alphabet size.…”
Section: ) Selection Of Alphabet Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Let the alphabet size be k = || and the method of partitioning the time series be maximum entropy partitioning [31], i.e., a uniform probability distribution on the symbols with Then, the information loss, represented by the negative of the entropy [21] of the symbol sequence, is given as (11) By representing the computational complexity as a function g(k) of the alphabet size k and choosing an appropriate scalar tradeoff weighting parameter a  (0, 1), the cost functional to be optimized becomes: (12) The optimal alphabet size || is obtained by solving for k in the equation J(k + 1) -J(k) = 0 along with additional constraints that may have to be imposed in the optimization procedure to realize the effects of critical issues such as any bounds on the alphabet size.…”
Section: ) Selection Of Alphabet Sizementioning
confidence: 99%
“…However, both Lieuwen et al and Gutmark demonstrated their techniques for LBO prediction in premixed combustors. On the other hand, Mukhopadhyay and coworkers [11], [12] developed a number of techniques for early detection of LBO, which worked satisfactorily over a wide range of fuel-air premixing. Chaudhari et al [11] used flame color to device a novel and inexpensive strategy for LBO detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flame visualization is considered as one of the important approaches to explore the dynamical behavior of the flame. 45 We show the typical flame images (captured by the digital CMOS camera) at different operating conditions (Φ/ΦLBO) of a premixed flame (using port F1) in Figure 3. At the equivalence ratios which are far from that corresponding to blowout, we observe a stable flame as the flame is anchored at the dump plane inside the combustor (see Figure.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a recent focus on LBO in partially premixed combustion (De et al ( , 2020c). Previously, researchers have used different techniques for LBO prediction (Chaudhari (2011); Muruganandam (2006); Chaudhari et al (2013); Unni and Sujith (2016)) As the operating limits to avoid the LBO regime cannot be easily determined during the design stage, it is important to develop online LBO detection frameworks which will be accurate and computationally faster. Some studies have focused on the computational time aspect of a lean blowout (Mukhopadhyay et al (2013); Sarkar et al (2015c); Dey et al (2015)).…”
Section: A Deep Learning Approach To Detect Lean Blowout In Combustio...mentioning
confidence: 99%